Republic of Uzbekistan : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2021)
Uzbekistan embarked on an ambitious reform path in 2017, starting to liberalize its economy after years of state control. Incomes are still relatively low compared to other emerging economies. Uzbekistan entered the COVID-19 crisis with relatively strong macro-economic fundamentals.